A short note on the legal aspects of auditing practice in Malaysia - Ng, Eng Juan (Penerbit Universiti Kebangsaan Malaysia, 1982)
This paper examines some of the legal aspects of auditing practice in Malaysia, such as: eligibility of being an auditor, appointment and retirement of auditor, duties, rights and liabilities of auditor. In the examination, references were made of the legislation being enforced in Malaysia, as well as some of the court decisions and professional pronouncemen ts of foreign countries.